2012
DOI: 10.1016/j.bbalip.2012.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics and regulation of lipid droplet formation in lipopolysaccharide (LPS)-stimulated microglia

Abstract: Lipid droplets (LDs) are neutral lipid-rich organelles involved in many cellular processes. A well-known example is their accumulation in leukocytes upon activation by pro-inflammatory stimuli such as lipopolysaccharides (LPS) derived from gram-negative bacteria. A role of LDs and LD-associated proteins during inflammation in the brain is unknown, however. We have now studied their dynamics and regulation in microglia, the resident immune cells in the brain. We find that LPS treatment of microglia leads to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
115
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(124 citation statements)
references
References 62 publications
9
115
0
Order By: Relevance
“…Our results show that pyrrolidine-2 pre-treatment dramatically increased the effectiveness of curcumin in U251N cells after 72 h, virtually abolishing cell viability at curcumin concentrations above 20 lM. Interestingly, the lipid droplet number of cells treated with curcumin following pyrrolidine-2 sensitization was higher than that of cells treated with curcumin alone -likely due to the drug-induced cellular stress, previously reported to induce lipid droplet formation [19,69,70]. Sensitization using BSO was comparatively less effective, likely due to the diversity of antioxidants and enzymes that can reduce ROS levels.…”
Section: Discussionmentioning
confidence: 65%
“…Our results show that pyrrolidine-2 pre-treatment dramatically increased the effectiveness of curcumin in U251N cells after 72 h, virtually abolishing cell viability at curcumin concentrations above 20 lM. Interestingly, the lipid droplet number of cells treated with curcumin following pyrrolidine-2 sensitization was higher than that of cells treated with curcumin alone -likely due to the drug-induced cellular stress, previously reported to induce lipid droplet formation [19,69,70]. Sensitization using BSO was comparatively less effective, likely due to the diversity of antioxidants and enzymes that can reduce ROS levels.…”
Section: Discussionmentioning
confidence: 65%
“…Likewise, cells depleted of cPLA 2 ␣ by RNA silencing result in the appearance of tubulo-vesicular profi les of the smooth endoplasmic reticulum, compatible with a role of cPLA 2 ␣ in regulating the structure of this organelle (11). cPLA 2 ␣ has recently been reported to translocate to LD after cell activation (24,25,63). Studies on cPLA 2 ␣ targeting to membranes have indicated that, in addition to increased Ca 2+ availability, there are other factors regulating the association of the enzyme to membranes, including the local concentration of phosphoinositides in the membrane (64,65) and the phosphorylation state of the cPLA 2 ␣ (66).…”
Section: Discussionmentioning
confidence: 83%
“…Several enzymes implicated in the biosynthesis of eicosanoids have been found to be associated with LDs under activation conditions, including cPLA 2 α [11][12][13]. Extracellular signal-regulated kinases-1 and -2, which can phosphorylate and activate cPLA 2 α, have also been found in LDs [11], as well as the major AA-converting enzymes 5-lipoxygenase, 15-lipoxygenase, 5-lipoxygenase-activating protein, and cyclooxygenase-2 [16,42].…”
Section: Pla 2 and Lipid Dropletsmentioning
confidence: 99%
“…Prominent proteins of mammalian LDs are the so-called PAT family, which includes perilipin, adipophilin and TIP47 (TailInteracting Protein of 47 kDa) [5]. Additionally, numerous enzymes related to lipid metabolism have been described, including adipose triglyceride lipase, hormone-sensitive lipase, CGI-58 (comparative gene identification-58) [6,7], CTP:phosphocholine cytidylyltransferase [8], lipin-1 [9,10], and group IVA phospholipase A 2 (cytosolic phospholipase A 2 α, cPLA 2 α) [11][12][13].…”
Section: Introductionmentioning
confidence: 99%